Students’ Perception in Learning English through Communicative English Club (CEC) at IAIN Salatiga - Eni Suriyah; Mazulfah (English Education and Literature Journal (E-Jou), 2022)
The purposes of this study were (1) to know how is perceptions of student in learning English through Communicative English Club (CEC) IAIN Salatiga and (2) to know how is the student’s perception of the stimulus for the English material given by the Communicative English Club (CEC) IAIN Salatiga. This study uses qualitative research to find out the purposes. Sample is chosen by the researcher or called a purposive sample. Six students who joined in Communicative English Club (CEC) were interviewed. From the results of this study, it is concluded that students who join the Communicative English Club (CEC) Student Activity Unit (UKM) had a positive perception of learning English at CEC and the materials that were given. CEC activities or work programs improve their English language skills, especially speaking skills. Although not aiming to learn English, students got an experience of learning English at CEC that is different from learning in the classroom. They got the opportunity to practice English more often. In addition, CEC provides environmental and mental support for learning English. Students consider English material to be not just written grammar material, but English material can be obtained through an environment, discussion, and experience that can improve their English language skills. Keywords: students’ perception, learning, English, English club